Streptococcus milleri and second trimester abortion. - MacGowan, A P (1987)
Review of 214 fetal necropsies performed in the department of pathology, University of Aberdeen, showed 40 cases of chorioamnionitis or intrauterine pneumonia, five of which were associated with Streptococcus milleri. In two cases there was good evidence to implicate S milleri as the cause of infected abortion while in the other cases its pathogenic role was less clear.